Art, littérature et anthropologie historique. Quelques réflexions historiographiques - Etienne Anheim (L'Atelier du CRH)
Literature and the arts, within historical anthropology, have raised questions related to historiography in the past thirty years. As they highlight tensions between the medieval and contemporary categories, underline recent shifts towards material documents and objects and confront anthropology with philosophy through aesthetics, artistic and literary practices unveil the reflexive and manifold dimensions underlying the use of anthropology by historians. As such, literature and the arts bear witness to methodological shifts dating from the 1970’s and show the extent of the ongoing progressive evolution in historical anthropology research agenda.